Evolutionary psychology, public policy, and personal decisions - Crawford, Charles (Charles B.); Salmon, Catherine (Lawrence Erlbaum Associates, 2004)
This volume's aim is to start the process of using theory and findings of evolutionary psychology to help make the world a better place to live. Taking evolutionary psychology explicitly into applied areas, it includes a reasonable scope of applications from pornography to psychopaths and from morality to sex differences in the workplace.